합성가스/디젤 혼소압축착화 엔진의 합성가스 혼합비와 압축비에 따른 연소 및 배출가스 특성 - 이준순; Junsun Lee; 정탄; Chung Tahn; 이용규; Yonggyu Lee; 김창업; Changup Kim; 오승묵; Seungmook Oh (한국분무공학회지, 2019)
Syngas is widely produced by incomplete combustion of coal, water vapor, and air (oxygen) in a high-temperature/highpressure gasifier through a coal-gasification process for power generation. In this study, a simulation syngas which was mainly composed of H 2 , CO, CO 2 , and N 2 was fueled with diesel. A modified single cylinder compression ignition (CI) engine is equipped with intake port syngas supply system and mechanical diesel direct injection system for dual fuel combustion. Combustion and emission characteristics of the engine were investigated by applying various syngas composition ratios and compression ratios. Diesel fuel injection timing was optimized to increase indicated thermal efficiency (ITE) at the engine speed 1,800 rpm and part load net indicated mean effective pressure (IMEP net ) 2 to 5 bar. ITE of the engine increased with the H 2 concentration, compression ratio and engine load. With 45% of H 2 concentration, compression ratio 17.1 and IMEP net 5 bar, ITE of 41.5% was achieved, which is equivalent to that of only diesel fuel operation.